1117. Avascular Necrosis of the Femoral Head as a Sequela of Shiga Toxin-producing Escherichia coli (STEC) Infection. (26th November 2018) - Stone-Garza, Kristi; Barlow, Brian; Maves, Ryan
Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) infection may be complicated by the hemolytic-uremic syndrome (HUS). Long-term sequelae of HUS are most often related to renovascular disease. Osteoarticular complications are rare. Avascular necrosis (AVN) has not been previously reported as a complication of STEC infection. Methods: We report two cases of United States Marine Corps (USMC) recruits who developed AVN of the femoral head following STEC infection during a large outbreak. Results: Between October and November 2017, an STEC outbreak occurred at Marine Corps Recruit Depot San Diego (MCRD-SD) affecting over 250 USMC recruits. Case 1: A 19-year-old recruit developed nine days of non-bloody diarrhea. Stool culture, Shiga toxin enzyme immunoassay (EIA), and polymerase chain reaction (PCR) demonstrated E. coli O157. Complete blood count (CBC) was normal 5 days after symptom resolution. One month after resolution of his infection, he developed right hip pain. Magnetic resonance imaging (MRI) revealed right femoral head AVN (Image 1). He was treated conservatively with nonsteroidal anti-inflammatory drug (NSAID) and physical therapy. Case 2: A 19-year-old recruit developed seven days of dysentery. Stool culture, Shiga toxin EIA and PCR demonstrated E. coli O157. He had a hemoglobin nadir of 8.0 g/dL and platelet nadir of 109 × 10 3 /microL. Renal function was normal except for mild proteinuria and microscopic hematuria. One month after resolution of his infection, he developed non-traumatic left hip pain. MRI revealed left femoral head AVN with subchondral collapse (Image 2). He completed three months of bisphosphonate therapy prior to his left hip core decompression and sub-chondroplasty. Conclusion: AVN of the hip is rare among healthy young adults and is not commonly observed in military recruits. We hypothesize that STEC-associated subclinical intravascular coagulopathy may cause microscopic occlusive disease. AVN should be considered in patients with new non-traumatic hip pain after known or suspected STEC infection. Disclosures: All authors: No reported disclosures.